Bioremoval of hazardous cobalt, nickel, chromium, copper and cadmium compounds from contaminated soil by Nicotiana tabacum plants and associated microbiome - Havryliuk, Olesia; Hovovrukha, Vira; Sachko, Anastasiia; Gladka, Galina; Bida, Iryna; Tashyrev, Oleksandr (My University, 2021)
Contamination of soils with heavy metals leads to reduction of soil fertility, destruction of natural ecosystems and detrimental effects on the health of society by increasing content of metals in the food chains from microorganisms to plants, animals and humans. Bioremed-iation is one of the most promising and cost-effective methods of cleaning soils polluted with toxic metals. According to current research-ers, microorganisms and plants have the genetic potential to remove toxic metals from contaminated sites. The method of thermodynamic prediction was used to theoretically substantiate the mechanisms of interaction of soil microorganisms and plants with heavy metals. According to the our prediction, exometabolite chelators of anaerobic microorganisms may increase the mobility of metals and thereby contribute to the active transport of metals and their accumulation in plants. Plants of Nicotiana tabacum L. of Djubek cultivar were used as plant material for the current investigation. The examined toxicants were heavy metals, namely cobalt (II), nickel (II), chromium (VI), copper (II) and cadmium (II). The aqueous solutions of metal salts were added to the boxes after two months of plants growing to the final super-high concentration – 500 mg/kg of absolutely dry weight of soil. Quantitative assessments of copper and chromium-resistant mi-croorganisms were made by cultivation on agar nutrient medium NA with a gradient of Cu(II) and Cr(VI). The concentration of metals in soil and plant material (leaves, stems and roots) was determined by atomic absorption method. The study revealed that heavy metals inhibited the growth of the examined tobacco plants. This was expressed by the necrosis of plant tissues and, ultimately, their complete death. Despite this, all investigated heavy metals were accumulated in plant tissues during 3–7 days before death of plants. The uptake of metals was observed in all parts of plants – leaves, stems and roots. The highest concentrations of Co(II), Ni(II), Cd(II), Cr(VI) were found in the leaves, Cu(II) – in the roots. The results show that the bioremoval efficiency of the investigated metals ranged 0.60–3.65%. Given the super-high initial concentration of each of the metals (500 mg/kg), the determined removal efficiency was also high. Cadmium was the most toxic to plants. Thus, the basic points of the thermodynamic prognosis of the possibility of accumulation of heavy metals by phytomicrobial consortium were experimentally confirmed on the example of N. tabacum plants and metal-resistant microorganisms. The study demonstrated that despite the high initial metals concentration, rate of damage and death of plants, metals are accumulated in plant tissues in extremely hight concentrations. Soil microorganisms were observed to have high adaptation potencial to Cu(II) and Cr(VI). In anaerobic conditions, microorganisms presumably mobilize heavy metals, which later are absorbed by plants. The obtained results are the basis for the development of environmental biotechnologies for cleaning contaminated soils from heavy metal compounds.
Keywords: thermodynamic prognosis; heavy metals contamination; metal-resistant microorganisms; environmental biotechnology